A new Benders decomposition approach to solve power transmission network design problems. - Binato, S. (IEEE Transactions on power systems)
In this paper we describe a new Benders decomposition approach to solve power transmission network expansion planning problems. This new approach is characterized by using a linear (0-1) disjuntctive model which ensures the optimality of the solution found and by using additional constraints, iteratively evaluated, besides the traditional Benders cuts. The results obtained, considering a real world power transmission network expansion planning study with the southeastern Brazilian system, show the efficiency of this approach